Effect of varying tartaric acid to metal nitrate ratio on the structure, morphology and magnetic properties of BaZn0.2Zr0.2Fe11.6O19 samples. Issue 6 (15th March 2022) - Godara, Sachin Kumar; Sood, Ashwani Kumar; Shilpi,; Kumar, Arun; Kaur, Varinder; Malhi, Parambir Singh; Singh, Mandeep; Verma, Swati; Batoo, Khalid Mujasam
Abstract: Here in, we report synthesis of BaZn0.2 Zr0.2 Fe11.6 O19 hexaferrite nanoparticles through the sol-gel auto-combustion route using tartaric acid as fuel. The nature of the fuel and fuel to metal nitrate ratio plays an important role in deciding the phase purity, grain size, shape, and magnetic properties of M-type hexaferrites. The optimization of the tartaric acid to metal nitrate (TA/MN) ratio was carried out by varying TA/MN ratios (0.00, 0.50, 0.75, 1.00, 1.25, and 1.50). XRD data revealed a single-phase M-type in samples synthesized using TA/MN ratio 0.50, 0.75, and 1.00 and the presence of α-Fe2 O3 as an impurity phase beyond 1.00 TA/MN ratio and in a standard sample (TA/MN ratio is 0.00) both α-Fe₂O₃ and BaFe2 O4 were found. FESEM micrographs revealed grain size continuously increases from 0.50 to 1.25 TA/MN ratio and decreases afterward for 1.50 TA/MN ratio. Magnetic measurements confirm that all the samples exhibit ferromagentic ordering. However, a kink along with wasp waist shape was observed in the samples synthesized using TA/MN ratio 0.00, 0.50, and 0.75 which may be due to presence of secondary phases/impurites and chemical inhomogeneity. The Hc was found to be minimum at 1.25 TA/MN ratio whereas Mr and Ms were found to be maximum at 1.00 TA/MN ratio. The optimum TA/MN ratio was found to be 1.00. These materials could be suitable for microwave absorber and magnetic recording applications due to their high Ms and low Hc values.